Lactose malabsorption in junior high school children - Aswitha D. Budiarso; Deny Sofia; Sri Rezeki S Hadinegoro; Badriul Hegar (Indonesian Pediatric Society, 2003)
Background The prevalence of lactose malabsorption varieswidely throughout the world. Only people of Caucasian geneticbackground continue to produce high amount of lactase throughoutadulthood. Previous studies in Indonesia revealed that theprevalence of lactose malabsorption was 21-58% in children aged3-11 years.Objective To determine the prevalence of lactose malabsorptionin the older age group and whether a change in milk drinking habitcan affect it.Methods A cross sectional descriptive study was conducted on98 children aged between 12 and 14 years (junior high school) inJakarta. Lactose malabsorption was evaluated with LactometerBreath Hydrogen Test (Hoek Loes, Amsterdam). Milk drinking habitwas recorded, and drinking at least 1 glass of milk everyday since6 months or more before the study was considered as regular milkdrinking.Results This study showed 73% of the children had lactose malabsorption.Regular milk drinking habit was found in 32 (33%) childrenand lactose malabsorption occurred in 26. From 66 childrenwho were irregular milk drinkers, lactose malabsorption was foundin 46 (70%). Lactose intolerance was about the same in both groups.Conclusion There was an increasing prevalence of lactose malabsorptionin older children. Milk drinking habit is a major concernto review the practical implications of lactose malabsorption.